Chemical, Mineralogical and Geotechnical Index Properties Characterization of Volcanic Ash Soils (2020)
Soils derived from volcanic ash are deposits formed from the weathering of the ejected material during volcanic activity. Volcanic ash is commonly known in geotechnical engineering as a difficult and unwanted material. The difficulties are related to the high-water content, high liquid limits, low unit weights, and high void ratios, which translates into possible engineering problems (e.g. compressibility and collapsibility). The characterization of these materials is important because volcanic soils represent 0.84% of the terrestrial soil surface, 60% of which are located in tropical zones. These percentages represent areas with a high human population and constant demographic and economic growth. This paper presents the chemical, mineralogical and geotechnical index properties characterization of soils derived from volcanic ashes through laboratory testing and compares them with the results found in the literature. The SEM results shows the high void reported in the literature. The index properties obtained coincide with the ranges reported. However, lower values of dry unit weight were observed, which are related to the transportation processes of the particles and with higher index properties values due to mineralogical components such as allophane. Therefore, the study of volcanic ash soils requires a rigorous knowledge and understanding of the soil formation, depositional environment, and mineralogy. The chemical characterization of the volcanic ash plays an important role to understand water retention characteristics and their influence on the different geotechnical properties. © 2020, Springer Nature Switzerland AG.